1998
DOI: 10.1073/pnas.95.17.10317
|View full text |Cite
|
Sign up to set email alerts
|

Altering hemoglobin levels changes energy status in maize cells under hypoxia

Abstract: Nonsymbiotic hemoglobins are broadly present across the plant kingdom; however, the function of these proteins is unknown. Cultured

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
147
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(152 citation statements)
references
References 23 publications
5
147
0
Order By: Relevance
“…In Arabidopsis the symbiotic-like ahb2 gene was expressed at low levels in rosette leaves and was induced by low temperatures, whereas the nonsymbiotic ahb1 gene was expressed in roots and rosette leaves and levels of expression increased under hypoxic conditions, suggesting that AHb1 is a stressrelated protein (Trevaskis et al, 1997), as has been well documented for barley Hb (Taylor et al, 1994;Hill, 1998). There is also some evidence that a signal transduction pathway involving calcium-dependent protein kinase(s) and protein phosphatase(s) may be involved in barley hb gene expression (R.D.…”
Section: Nonsymbiotic Hbs Are Expressed In Diverse Plant Tissuesmentioning
confidence: 80%
See 2 more Smart Citations
“…In Arabidopsis the symbiotic-like ahb2 gene was expressed at low levels in rosette leaves and was induced by low temperatures, whereas the nonsymbiotic ahb1 gene was expressed in roots and rosette leaves and levels of expression increased under hypoxic conditions, suggesting that AHb1 is a stressrelated protein (Trevaskis et al, 1997), as has been well documented for barley Hb (Taylor et al, 1994;Hill, 1998). There is also some evidence that a signal transduction pathway involving calcium-dependent protein kinase(s) and protein phosphatase(s) may be involved in barley hb gene expression (R.D.…”
Section: Nonsymbiotic Hbs Are Expressed In Diverse Plant Tissuesmentioning
confidence: 80%
“…The other group of plant Hbs, nonsymbiotic Hbs, appear to be ancestral to the symbiotic Hbs, are more widespread in the plant kingdom, and generally display a high affinity for oxygen. Their function in plants is the subject of much current inquiry (Appleby, 1992;Andersson et al, 1996;Arredondo-Peter et al, 1997a;Trevaskis et al, 1997;Hill, 1998). Some aspects of plant nonsymbiotic Hb function, particularly that of barley, have been succinctly reviewed by Hill (1998).…”
Section: Symbiotic and Nonsymbiotic Plant Hbs Belong To A Large Familmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the studies on over- and under-expressing barley nsHb in maize cells, it was proposed that under hypoxic conditions barley nsHb is involved in the ATP metabolism, particularly in maintaining the energy status under O 2 -limiting conditions 136 . Immunolocalization data showed that rice Hbs are localized in differentiating cells (see subsection on Gene expression and localization of hemoglobins in rice organs ) 70 .…”
Section: Postulated Functions For Rice Hemoglobinsmentioning
confidence: 99%
“…Although the function of nsHbs is still not known, recent work suggests that these proteins play important roles in plant metabolism. For example, it has been proposed that barley nsHb functions by modulating the energy status and NO-levels in transgenic maize cells [23] and stressed alfalfa root cultures [10], respectively.…”
Section: Introductionmentioning
confidence: 99%